Conductive particles, conductive materials and connection structures
By introducing conductive metal into the matrix particles of small-particle conductive particles and forming a thin conductive layer, the problem in the prior art is solved that it is difficult to simultaneously reduce connection resistance and suppress the aggregation of conductive particles, and lower connection resistance and higher insulation reliability are achieved.
Patent Information
- Application Number
- JP2020538860
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-28
- Filing Date
- 2020-02-28
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2040-02-28
AI Technical Summary
The prior art is difficult to simultaneously reduce the connection resistance and suppress the aggregation of conductive particles in small-particle conductive particles, resulting in difficulty in improving the insulation reliability between electrodes.
A matrix particle containing a conductive metal is used and a thin conductive layer is formed on its surface. The connection resistance is reduced through the conductive metal path within the matrix particle, while the particle aggregation is suppressed by the thinness of the conductive layer.
It effectively reduces the connection resistance between electrodes, and improves the insulation reliability between electrodes, avoiding unnecessary electrode connections.
Smart Images

Figure 0007671142000005 
Figure 0007671142000006 
Figure 0007671142000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive particle having a conductive portion disposed on the surface of a base particle. The present invention also relates to a conductive material and a connection structure using the conductive particle. [Background technology]
[0002] Anisotropic conductive materials such as anisotropic conductive pastes and anisotropic conductive films are widely known. In the anisotropic conductive materials, conductive particles are dispersed in a binder resin. In addition, as the conductive particles, conductive particles having a base particle and a conductive portion disposed on the surface of the base particle may be used.
[0003] The anisotropic conductive material is used to obtain various connection structures. Examples of connections using the anisotropic conductive material include a connection between a flexible printed circuit board and a glass substrate (FOG (Film on Glass)), a connection between a semiconductor chip and a flexible printed circuit board (COF (Chip on Film)), a connection between a semiconductor chip and a glass substrate (COG (Chip on Glass)), and a connection between a flexible printed circuit board and a glass epoxy substrate (FOB (Film on Board)).
[0004] As an example of the conductive particles, the following Patent Document 1 discloses conductive particles comprising a nickel layer and a gold layer formed on the nickel layer. The average thickness of the gold layer is 300 Å or less. In this conductive particle, the gold layer is the outermost layer. Furthermore, in this conductive particle, the elemental composition ratio of nickel to gold (Ni / Au) on the surface of the conductive particle by X-ray photoelectron spectroscopy analysis is 0.4 or less.
[0005] The following Patent Document 2 discloses a conductive particle including a core particle, a Ni plating layer, a precious metal plating layer, and an anti-rust film. The Ni plating layer covers the core particle. The precious metal plating layer covers at least a part of the Ni plating layer. The precious metal plating layer contains at least one of Au and Pd. The anti-rust film covers at least one of the Ni plating layer and the precious metal plating layer. The anti-rust film contains an organic compound. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-102731 A [Patent Document 2] JP 2013-20721 A Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, in conductive materials containing conductive particles, the particle size of conductive particles has been reduced due to finer pitches in wiring and connectors in printed wiring boards and the like.
[0008] When electrodes are connected to each other using conductive particles with a small particle diameter to prepare a connection structure, the thickness of the conductive part of the conductive particles may be increased in order to sufficiently reduce the connection resistance between the electrodes in the vertical direction. However, when the thickness of the conductive part is increased, the conductive particles may aggregate when the conductive part is formed by plating. When the conductive particles aggregate, the electrodes adjacent in the horizontal direction tend to be easily connected, and it may be difficult to improve the insulation reliability between the electrodes adjacent in the horizontal direction.
[0009] In addition, if the thickness of the conductive part is reduced in order to suppress the aggregation of the conductive particles, the aggregation of the conductive particles can be suppressed when the conductive part is formed by plating, but it becomes difficult to sufficiently reduce the connection resistance between the electrodes in the vertical direction. With conventional conductive particles, it is difficult to simultaneously reduce the connection resistance between the electrodes and suppress the occurrence of aggregation of the conductive particles.
[0010] An object of the present invention is to provide a conductive particle that can effectively reduce the connection resistance between electrodes and can effectively suppress the occurrence of aggregation between the conductive particles. Another object of the present invention is to provide a conductive material and a connection structure using the conductive particle. [Means for solving the problem]
[0011] According to a broad aspect of the present invention, there is provided a conductive particle comprising a substrate particle and a conductive portion disposed on a surface of the substrate particle, the substrate particle containing a conductive metal within the substrate particle.
[0012] In a specific aspect of the conductive particle according to the present invention, the base particle has a porosity of 10% or more.
[0013] In a specific aspect of the conductive particle according to the present invention, the conductive metal includes nickel, gold, palladium, silver, or copper.
[0014] In a specific aspect of the conductive particle according to the present invention, the conductive portion contains nickel, gold, palladium, silver, or copper.
[0015] In a specific aspect of the conductive particle according to the present invention, the 10% K value of the conductive particle is 100 N / mm 2 More than 25000N / mm 2 The following is the result.
[0016] In a specific aspect of the conductive particle according to the present invention, the 30% K value of the conductive particle is 100 N / mm 2 More than 15000N / mm2 The following is the result.
[0017] In a specific aspect of the conductive particle according to the present invention, a ratio of a 10% K value of the conductive particle to a 30% K value of the conductive particle is 1.5 or more and 5 or less.
[0018] In a specific aspect of the conductive particle according to the present invention, the conductive particle has a particle diameter of 0.1 μm or more and 1000 μm or less.
[0019] In a specific aspect of the conductive particle according to the present invention, the content of the conductive metal contained in the base particle is 0.1 vol % or more and 30 vol % or less, relative to 100 vol % of the conductive particle.
[0020] In a specific aspect of the conductive particle according to the present invention, the conductive particle has protrusions on an outer surface of the conductive portion.
[0021] In a specific aspect of the conductive particle according to the present invention, the conductive particle includes an insulating material disposed on an outer surface of the conductive portion.
[0022] According to a broad aspect of the present invention, there is provided a conductive material including the above-described conductive particles and a binder resin.
[0023] In a specific aspect of the conductive material according to the present invention, the conductive material contains a plurality of the conductive particles, and when a region R1 is defined as a region from the outer surface of the base particle toward the center at a distance of 1 / 2 the particle diameter of the base particle, the proportion of the number of conductive particles in which the conductive metal is present in the region R1 of the base particle out of the total number of the conductive particles (100%) is 50% or more.
[0024] In a specific aspect of the conductive material according to the present invention, the conductive material includes a plurality of the conductive particles, and when a region R2 is defined as a region from the center of the base particle toward the outer surface at a distance of 1 / 2 the particle diameter of the base particle, the proportion of the number of conductive particles in which the conductive metal is present in the region R2 of the base particle out of the total number of the conductive particles (100%) is 5% or more.
[0025] According to a broad aspect of the present invention, there is provided a connection structure comprising a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection portion connecting the first connection target member and the second connection target member, wherein the material of the connection portion is the conductive particles described above or a conductive material containing the conductive particles and a binder resin, and the first electrode and the second electrode are electrically connected by the conductive particles. Effect of the Invention
[0026] The conductive particle according to the present invention comprises a base particle and a conductive portion disposed on the surface of the base particle. In the conductive particle according to the present invention, the base particle contains a conductive metal inside the base particle. Since the conductive particle according to the present invention has the above-mentioned configuration, the connection resistance between electrodes can be effectively reduced and the occurrence of aggregation between the conductive particles can be effectively suppressed. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention. [Figure 4] FIG. 4 is a schematic diagram for explaining each region in the base particle where the presence or absence of a conductive metal is confirmed. [Diagram 5]FIG. 5 is a front cross-sectional view that typically shows a connection structure using conductive particles according to the first embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The present invention will be described in detail below.
[0029] (Conductive particles) The conductive particle according to the present invention includes a base particle and a conductive portion disposed on a surface of the base particle. In the conductive particle according to the present invention, the base particle contains a conductive metal inside the base particle.
[0030] Since the conductive particles according to the present invention have the above-mentioned configuration, the connection resistance between electrodes can be effectively reduced and the occurrence of aggregation between the conductive particles can be effectively suppressed.
[0031] When electrodes are connected to each other using conductive particles with a small particle diameter to prepare a connection structure, the thickness of the conductive part of the conductive particles may be increased in order to sufficiently reduce the connection resistance between the electrodes in the vertical direction. However, when the thickness of the conductive part is increased, the conductive particles may aggregate when the conductive part is formed by plating. When the conductive particles aggregate, the electrodes adjacent in the horizontal direction tend to be easily connected, and it may be difficult to improve the insulation reliability between the electrodes adjacent in the horizontal direction.
[0032] In addition, if the thickness of the conductive part is reduced in order to suppress the aggregation of the conductive particles, the aggregation of the conductive particles can be suppressed when the conductive part is formed by plating, but it becomes difficult to sufficiently reduce the connection resistance between the upper and lower electrodes. With conventional conductive particles, it is difficult to simultaneously reduce the connection resistance between the electrodes and suppress the occurrence of aggregation of the conductive particles.
[0033] The present inventors have found that by using specific conductive particles, it is possible to achieve both a reduction in the connection resistance between electrodes and a suppression of the occurrence of aggregation between conductive particles. In the present invention, when the electrodes in the vertical direction are connected, the conductive particles are compressed, so that not only a conductive path is formed on the surface (conductive portion) of the conductive particles, but also a conductive path can be formed inside the conductive particles (conductive metal). In addition, the conductive metal inside the conductive particles contributes to reducing the connection resistance to a certain extent even if it does not form a complete conductive path. As a result, even if the thickness of the conductive portion is relatively thin, the connection resistance between the electrodes in the vertical direction can be sufficiently reduced. In addition, since the thickness of the conductive portion is relatively thin, the occurrence of aggregation between the conductive particles can be suppressed, and the insulation reliability between the horizontally adjacent electrodes that should not be connected can be effectively improved. In the present invention, since the above-mentioned configuration is provided, the connection resistance between the electrodes can be effectively reduced and the occurrence of aggregation between the conductive particles can be effectively suppressed. In addition, in the present invention, a conductive path (conductive portion) is formed not only on the surface of the base particle but also inside the base particle, and the conductive path (conductive portion) can penetrate into the inside of the base particle. As a result, the adhesion of the conductive portion of the conductive particle can be effectively increased, and peeling of the conductive portion of the conductive particle can be effectively suppressed.
[0034] In the present invention, the use of specific conductive particles greatly contributes to obtaining the above-mentioned effects.
[0035] The 10% K value (compressive elastic modulus when compressed by 10%) of the conductive particles is preferably 100 N / mm 2 More preferably, 1000N / mm 2 or more, preferably 25000N / mm 2 Less than or equal to 20,000 N / mm 2 When the 10% K value of the conductive particles is equal to or greater than the lower limit and equal to or less than the upper limit, the connection resistance between electrodes can be more effectively reduced, the occurrence of cracks in the conductive particles can be more effectively suppressed, and the connection reliability between the electrodes can be more effectively improved.
[0036] The 30% K value (compressive elastic modulus when compressed by 30%) of the conductive particles is preferably 100 N / mm 2 More preferably, 1000N / mm 2 or more, preferably 15000N / mm 2 Less than or equal to 10,000 N / mm 2 When the 30% K value of the conductive particles is equal to or greater than the lower limit and equal to or less than the upper limit, the connection resistance between electrodes can be more effectively reduced, the occurrence of cracks in the conductive particles can be more effectively suppressed, and the connection reliability between the electrodes can be more effectively improved.
[0037] The ratio of the 10% K value of the conductive particles to the 30% K value of the conductive particles (10% K value of conductive particles / 30% K value of conductive particles) is preferably 1.5 or more, more preferably 1.55 or more, and preferably 5 or less, more preferably 4.5 or less. When the ratio (10% K value of conductive particles / 30% K value of conductive particles) is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between electrodes can be more effectively reduced, the occurrence of cracks in the conductive particles can be more effectively suppressed, and the connection reliability between the electrodes can be more effectively improved.
[0038] The 10% K value and the 30% K value of the conductive particles can be measured as follows.
[0039] Using a micro-compression tester, one conductive particle is compressed with a cylindrical (diameter 100 μm, made of diamond) smooth indenter end face under the conditions of 25° C., compression speed 0.3 mN / sec, and maximum test load 20 mN. The load value (N) and compression displacement (mm) at this time are measured. From the obtained measured values, the above-mentioned compression elastic modulus (10% K value and 30% K value) can be calculated by the following formula. As the above-mentioned micro-compression tester, a Fisherscope H-100 manufactured by Fisher Co., Ltd. or the like is used. The above-mentioned 10% K value and the above-mentioned 30% K value of the above-mentioned conductive particle are preferably calculated by arithmetic averaging of the 10% K value and the 30% K value of 50 arbitrarily selected conductive particles.
[0040] 10%K value and 30%K value (N / mm 2 )=(3 / 2 1 / 2 )·F·S -3 / 2 ·R - 1 / 2 F: Load value (N) when the conductive particles are compressed by 10% or 30% S: Compressive displacement (mm) when the conductive particles are compressed by 10% or 30% R: Radius of conductive particle (mm)
[0041] The compressive elastic modulus universally and quantitatively represents the hardness of the conductive particles. The compressive elastic modulus can be used to quantitatively and unambiguously represent the hardness of the conductive particles. In addition, the ratio (10% K value of the conductive particles / 30% K value of the conductive particles) can quantitatively and unambiguously represent the physical properties of the conductive particles at the time of initial compression.
[0042] The particle diameter of the conductive particles is preferably 0.1 μm or more, more preferably 1 μm or more, and preferably 1000 μm or less, more preferably 10 μm or less. If the particle diameter of the conductive particles is above the lower limit and below the upper limit, when the conductive particles are used to connect electrodes, the contact area between the conductive particles and the electrodes is sufficiently large, and the conductive particles are less likely to aggregate when forming the conductive part. In addition, the gap between the electrodes connected via the conductive particles is not too large, and the conductive part is less likely to peel off from the surface of the base particle.
[0043] The particle diameter of the conductive particles is preferably an average particle diameter, and is preferably a number average particle diameter. The particle diameter of the conductive particles is, for example, obtained by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average particle diameter of each conductive particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or an optical microscope, the particle diameter of each conductive particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary conductive particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each conductive particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the conductive particles is preferably calculated using a particle size distribution measuring device.
[0044] The conductive particles preferably have a particle size variation coefficient (CV value) of 10% or less, more preferably 5% or less. When the conductive particles have a particle size variation coefficient of the upper limit or less, the electrical continuity reliability and insulation reliability between electrodes can be more effectively improved.
[0045] The coefficient of variation (CV value) can be measured as follows.
[0046] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of the particle size of the conductive particles Dn: Average particle size of conductive particles
[0047] The shape of the conductive particles is not particularly limited, and may be spherical or a shape other than spherical, such as flat.
[0048] The present invention will now be described in detail with reference to the drawings.
[0049] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention.
[0050] The conductive particle 1 shown in Fig. 1 has a base particle 2 and a conductive portion 3. The conductive portion 3 is disposed on the surface of the base particle 2. In the first embodiment, the conductive portion 3 is in contact with the surface of the base particle 2. The conductive particle 1 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 3.
[0051] In the conductive particle 1, the conductive portion 3 is a single-layer conductive layer. In the conductive particle 1, the base particle 2 contains a conductive metal inside the base particle 2. In the conductive particle, the conductive portion may cover the entire surface of the base particle, or the conductive portion may cover a part of the surface of the base particle. In the conductive particle, the conductive portion may be a single-layer conductive layer, or may be a multi-layer conductive layer composed of two or more layers.
[0052] Unlike conductive particles 11 and 21 described later, conductive particle 1 does not have a core material. Conductive particle 1 does not have protrusions on its surface. Conductive particle 1 is spherical. Conductive portion 3 does not have protrusions on its outer surface. In this way, the conductive particle according to the present invention may not have protrusions on its conductive surface and may be spherical. Moreover, unlike conductive particles 11 and 21 described later, conductive particle 1 does not have an insulating material. However, conductive particle 1 may have an insulating material disposed on the outer surface of conductive portion 3.
[0053] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention.
[0054] 2 includes a base particle 2, a conductive portion 12, a plurality of core materials 13, and a plurality of insulating materials 14. The conductive portion 12 is disposed on the surface of the base particle 2 so as to be in contact with the base particle 2.
[0055] In the conductive particle 11, the conductive portion 12 is a single-layer conductive layer. In the conductive particle 11, the base particle 2 contains a conductive metal inside the base particle 2. In the conductive particle, the conductive portion may cover the entire surface of the base particle, or the conductive portion may cover a part of the surface of the base particle. In the conductive particle, the conductive portion may be a single-layer conductive layer, or may be a multi-layer conductive layer composed of two or more layers.
[0056] The conductive particle 11 has a plurality of protrusions 11a on its conductive surface. The conductive portion 12 has a plurality of protrusions 12a on its outer surface. A plurality of core substances 13 are disposed on the surface of the base particle 2. The plurality of core substances 13 are embedded in the conductive portion 12. The core substances 13 are disposed inside the protrusions 11a, 12a. The conductive portion 12 covers the plurality of core substances 13. The outer surface of the conductive portion 12 is raised by the plurality of core substances 13, forming the protrusions 11a, 12a.
[0057] The conductive particle 11 has an insulating material 14 disposed on the outer surface of the conductive portion 12. At least a portion of the outer surface of the conductive portion 12 is covered with the insulating material 14. The insulating material 14 is formed of a material having insulating properties, and is an insulating particle. In this way, the conductive particle according to the present invention may have an insulating material disposed on the outer surface of the conductive portion. However, the conductive particle according to the present invention does not necessarily have to have an insulating material.
[0058] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention.
[0059] 3 has a base particle 2, a conductive portion 22, a plurality of core materials 13, and a plurality of insulating materials 14. The conductive portion 22 as a whole has a first conductive portion 22A on the base particle 2 side, and a second conductive portion 22B on the side opposite to the base particle 2 side.
[0060] The only difference between conductive particle 11 and conductive particle 21 is the conductive portion. That is, conductive particle 11 has conductive portion 12 with a single layer structure, whereas conductive particle 21 has first conductive portion 22A and second conductive portion 22B with a two-layer structure. First conductive portion 22A and second conductive portion 22B are formed as separate conductive portions.
[0061] The first conductive portion 22A is disposed on the surface of the base particle 2. The first conductive portion 22A is disposed between the base particle 2 and the second conductive portion 22B. The first conductive portion 22A is in contact with the base particle 2. The second conductive portion 22B is in contact with the first conductive portion 22A. Therefore, the first conductive portion 22A is disposed on the surface of the base particle 2, and the second conductive portion 22B is disposed on the surface of the first conductive portion 22A. The conductive particle 21 has a plurality of protrusions 21a on its conductive surface. The conductive portion 22 has a plurality of protrusions 22a on its outer surface. The first conductive portion 22A has a plurality of protrusions 22Aa on its outer surface. The second conductive portion 22B has a plurality of protrusions 22Ba on its outer surface.
[0062] Other details of the conductive particles will be described below.
[0063] (base material particles) The material of the base particle is not particularly limited. The material of the base particle may be an organic material or an inorganic material. Examples of the base particle formed only from the organic material include resin particles. Examples of the base particle formed only from the inorganic material include inorganic particles other than metals. Examples of the base particle formed from both the organic material and the inorganic material include organic-inorganic hybrid particles. From the viewpoint of further improving the compression characteristics of the base particle, the base particle is preferably a resin particle or an organic-inorganic hybrid particle, and more preferably a resin particle.
[0064] Examples of the organic material include polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyether ether ketone, polyether sulfone, divinylbenzene polymer, and divinylbenzene copolymer. Examples of the divinylbenzene copolymer include divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylic acid ester copolymer. The material of the base particle is preferably a polymer obtained by polymerizing one or more polymerizable monomers having an ethylenically unsaturated group, since the compression characteristics of the base particle can be easily controlled within a suitable range.
[0065] When the base particle is obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, the polymerizable monomer having an ethylenically unsaturated group includes a non-crosslinkable monomer and a crosslinkable monomer.
[0066] Examples of the non-crosslinkable monomer include vinyl compounds such as styrene monomers, α-methylstyrene, and chlorostyrene; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; halogen-containing monomers such as vinyl chloride and vinyl fluoride; and (meth)acrylic compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl Examples of suitable (meth)acrylate compounds include alkyl (meth)acrylate compounds such as (meth)acrylate and isobornyl (meth)acrylate; oxygen-containing (meth)acrylate compounds such as 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; halogen-containing (meth)acrylate compounds such as trifluoromethyl (meth)acrylate and pentafluoroethyl (meth)acrylate; α-olefin compounds such as diisobutylene, isobutylene, linearne, ethylene, and propylene; and conjugated diene compounds such as isoprene and butadiene.
[0067] Examples of the crosslinkable monomer include vinyl compounds such as vinyl monomers, e.g., divinylbenzene, 1,4-divinyloxybutane, and divinylsulfone; (meth)acrylic compounds such as polyfunctional (meth)acrylate compounds, e.g., tetramethylolmethane tetra(meth)acrylate, polytetramethylene glycol diacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; and allyl compounds. Examples of the silane compounds include silane alkoxide compounds such as tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, isopropyltrimethoxysilane, isobutyltrimethoxysilane, cyclohexyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, 1,3-divinyltetramethyldisiloxane, methylphenyldimethoxysilane, and diphenyldimethoxysilane;Examples of the silane alkoxides include silanes containing polymerizable double bonds, such as vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, dimethoxyethylvinylsilane, diethoxymethylvinylsilane, diethoxyethylvinylsilane, ethylmethyldivinylsilane, methylvinyldimethoxysilane, ethylvinyldimethoxysilane, methylvinyldiethoxysilane, ethylvinyldiethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane; cyclic siloxanes such as decamethylcyclopentasiloxane; modified (reactive) silicone oils such as one-end modified silicone oil, both-end silicone oil, and side-chain silicone oil; and carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride.
[0068] The base particle can be obtained by polymerizing the polymerizable monomer having the ethylenically unsaturated group.The polymerization method is not particularly limited, and includes known methods such as radical polymerization, ionic polymerization, polycondensation (condensation polymerization, condensation polymerization), addition condensation, living polymerization, and living radical polymerization.Another polymerization method includes suspension polymerization in the presence of a radical polymerization initiator.
[0069] Examples of the inorganic material include silica, alumina, barium titanate, zirconia, carbon black, silicate glass, borosilicate glass, lead glass, soda-lime glass, and alumina silicate glass.
[0070] The base particle may be an organic-inorganic hybrid particle. The base particle may be a core-shell particle. When the base particle is an organic-inorganic hybrid particle, examples of the inorganic material of the base particle include silica, alumina, barium titanate, zirconia, and carbon black. The inorganic material is preferably not a metal. The base particle formed of silica is not particularly limited, but examples include base particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form crosslinked polymer particles, and then baking the resulting particles as necessary. The organic-inorganic hybrid particle may be an organic-inorganic hybrid particle formed of a crosslinked alkoxysilyl polymer and an acrylic resin.
[0071] The organic-inorganic hybrid particles are preferably core-shell type organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. The base particle is preferably an organic-inorganic hybrid particle having an organic core and an inorganic shell disposed on the surface of the organic core.
[0072] Examples of the material for the organic core include the organic materials described above.
[0073] The material of the inorganic shell may be any of the inorganic substances listed as the material of the base particle. The material of the inorganic shell is preferably silica. The inorganic shell is preferably formed by forming a shell-like material from a metal alkoxide on the surface of the core by a sol-gel method, and then firing the shell-like material. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed from a silane alkoxide.
[0074] The BET specific surface area of the base particles is preferably 8 m 2 / g or more, more preferably 12m 2 / g or more, preferably 1200m2 / g or less, more preferably 1000m 2 / g or less. When the BET specific surface area is equal to or more than the lower limit and equal to or less than the upper limit, the conductive metal can be more easily contained inside the base particle. When the BET specific surface area is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the BET specific surface area is equal to or more than the lower limit and equal to or less than the upper limit, the insulation reliability between the electrodes can be more effectively improved. When the BET specific surface area is equal to or more than the lower limit and equal to or less than the upper limit, the adhesion of the conductive part in the conductive particle can be more effectively increased, and the occurrence of peeling of the conductive part in the conductive particle can be more effectively suppressed.
[0075] The BET specific surface area of the base material particles can be measured from a nitrogen adsorption isotherm according to the BET method. Examples of a measuring device for the BET specific surface area of the base material particles include "NOVA4200e" manufactured by Quantachrome Instruments.
[0076] The total pore volume of the substrate particles is preferably less than 0.01 cm 3 / g or more, more preferably 0.1 cm 3 / g or more, preferably 3 cm 3 / g or less, more preferably 1.5 cm 3 / g or less. When the total pore volume is equal to or more than the lower limit and equal to or less than the upper limit, the conductive metal can be more easily contained inside the base particle. When the total pore volume is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the total pore volume is equal to or more than the lower limit and equal to or less than the upper limit, the insulation reliability between the electrodes can be more effectively improved. When the total pore volume is equal to or more than the lower limit and equal to or less than the upper limit, the adhesion of the conductive part in the conductive particle can be more effectively increased, and the occurrence of peeling of the conductive part in the conductive particle can be more effectively suppressed.
[0077] The total pore volume of the base particle can be measured from a nitrogen adsorption isotherm according to the BJH method. Examples of a device for measuring the total pore volume of the base particle include "NOVA4200e" manufactured by Quantachrome Instruments.
[0078] The average pore diameter of the base particle is preferably 10 nm or less, more preferably 5 nm or less. The lower limit of the average pore diameter of the base particle is not particularly limited. The average pore diameter of the base particle may be 1 nm or more. When the average pore diameter is equal to or greater than the lower limit and equal to or less than the upper limit, the conductive metal can be more easily contained inside the base particle. When the average pore diameter is equal to or greater than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. In addition, when the average pore diameter is equal to or greater than the lower limit and equal to or less than the upper limit, the insulation reliability between the electrodes can be more effectively improved. In addition, when the average pore diameter is equal to or greater than the lower limit and equal to or less than the upper limit, the adhesion of the conductive part in the conductive particle can be more effectively increased, and the occurrence of peeling of the conductive part in the conductive particle can be more effectively suppressed.
[0079] The average pore size of the base particles can be measured from a nitrogen adsorption isotherm according to the BJH method. Examples of a device for measuring the average pore size of the base particles include "NOVA4200e" manufactured by Quantachrome Instruments.
[0080] The porosity of the base particle is preferably 5% or more, more preferably 10% or more, and preferably 90% or less, more preferably 70% or less. When the porosity is equal to or more than the lower limit and equal to or less than the upper limit, the conductive metal can be more easily contained inside the base particle. When the porosity is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. In addition, when the porosity is equal to or more than the lower limit and equal to or less than the upper limit, the insulation reliability between the electrodes can be more effectively improved. In addition, when the porosity is equal to or more than the lower limit and equal to or less than the upper limit, the adhesion of the conductive part of the conductive particle can be more effectively increased, and the occurrence of peeling of the conductive part of the conductive particle can be more effectively suppressed.
[0081] The porosity of the base material particles can be calculated by measuring the cumulative amount of mercury intrusion against the applied pressure using mercury intrusion porosimetry. Examples of a device for measuring the porosity of the base material particles include the mercury porosimeter "Poremaster 60" manufactured by Quantachrome Instruments.
[0082] The base particle satisfying the preferred ranges of the BET specific surface area and the porosity can be obtained, for example, by a method for producing base particles comprising the following steps. A step of mixing a polymerizable monomer with an organic solvent that does not react with the polymerizable monomer to prepare a polymerizable monomer solution. A step of adding the polymerizable monomer solution and an anionic dispersion stabilizer to a polar solvent and emulsifying to obtain an emulsion. A step of adding the emulsion in several batches to absorb the monomer into seed particles to obtain a suspension containing seed particles in which the monomer is swollen. A step of polymerizing the polymerizable monomer to obtain base particles. Examples of the polymerizable monomer include monofunctional monomers and polyfunctional monomers. The organic solvent that does not react with the polymerizable monomer is not particularly limited as long as it is incompatible with polar solvents such as water, which is the medium of the polymerization system. Examples of the organic solvent include cyclohexane, toluene, xylene, ethyl acetate, butyl acetate, allyl acetate, propyl acetate, chloroform, methylcyclohexane, and methyl ethyl ketone. The amount of the organic solvent added is preferably 105 to 215 parts by weight, and more preferably 110 to 210 parts by weight, relative to 100 parts by weight of the polymerizable monomer component. When the amount of the organic solvent added is within the above preferred range, the BET specific surface area, porosity, and the like can be controlled within more suitable ranges, making it easier to obtain dense pores inside the particles.
[0083] The base particle satisfying the preferred ranges of the BET specific surface area and the porosity has a relatively large number of voids inside the base particle, so that when the conductive part is formed on the surface of the base particle, the conductive part enters the fine voids inside the base particle, and the conductive metal can be easily contained inside the base particle. Furthermore, in the conductive particle, it is preferable that the conductive particles are compressed when connecting the electrodes in the upper and lower directions, so that the conductive metals inside the base particle come into contact with each other to form a conductive path. In the conductive particle, not only is a conductive path formed on the surface (conductive part) of the conductive particle, but also a conductive path is formed inside the conductive particle (conductive metal). As a result, even if the thickness of the conductive part is relatively thin, the connection resistance between the electrodes in the upper and lower directions can be sufficiently reduced. In addition, since the thickness of the conductive part is relatively thin, the occurrence of aggregation of the conductive particles can be suppressed, and the insulation reliability between the horizontally adjacent electrodes that should not be connected can be effectively improved. Furthermore, in the above-mentioned conductive particles, when the conductive portion is formed on the surface of the base particle, the conductive portion penetrates into the minute gaps inside the base particle, so that the adhesion of the conductive portion in the conductive particle can be effectively increased and peeling of the conductive portion in the conductive particle can be effectively suppressed.
[0084] The particle diameter of the base particle is preferably 0.1 μm or more, more preferably 1 μm or more. The particle diameter of the base particle is preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 300 μm or less, even more preferably 50 μm or less, and even more preferably 10 μm or less. When the particle diameter of the base particle is above the lower limit, the contact area between the conductive particles and the electrodes is increased, so that the reliability of conduction between the electrodes can be further improved, and the connection resistance between the electrodes connected via the conductive particles can be further reduced. Furthermore, when forming a conductive portion on the surface of the base particle by electroless plating, it is possible to make it difficult for aggregated conductive particles to be formed. When the particle diameter of the base particle is below the upper limit, the conductive particles are easily compressed sufficiently, the connection resistance between the electrodes can be further reduced, and the gap between the electrodes can be further reduced.
[0085] The particle diameter of the base particle is particularly preferably 1 μm or more and 3 μm or less. When the particle diameter of the base particle is within the range of 1 μm or more and 3 μm or less, aggregation is unlikely to occur when forming the conductive portion on the surface of the base particle, and aggregated conductive particles are unlikely to be formed.
[0086] The particle diameter of the base particle indicates the number average particle diameter. The particle diameter of the base particle is obtained by observing 50 arbitrary base particles with an electron microscope or optical microscope and calculating the average particle diameter of each base particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or optical microscope, the particle diameter of each base particle is obtained as the particle diameter of a circle equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle diameter of 50 arbitrary base particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each base particle is obtained as the particle diameter of a sphere equivalent diameter. The average particle diameter of the base particles is preferably calculated using a particle size distribution measuring device. When the particle diameter of the base particles in the conductive particles is measured, it can be measured, for example, as follows.
[0087] The conductive particles are added to Kulzer's Technovit 4000 so that the content of the conductive particles is 30% by weight, and dispersed to prepare a conductive particle inspection embedding resin. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the conductive particles dispersed in the inspection embedding resin. Then, using a field emission scanning electron microscope (FE-SEM), the image magnification is set to 25,000 times, 50 conductive particles are randomly selected, and the base particle of each conductive particle is observed. The particle diameter of the base particle in each conductive particle is measured, and the arithmetic average of the measured particle diameters is determined as the particle diameter of the base particle.
[0088] (Conductive parts and conductive metals) The conductive particle according to the present invention comprises a base particle and a conductive portion disposed on the surface of the base particle. In the conductive particle according to the present invention, the base particle contains a conductive metal inside the base particle. The conductive portion preferably contains a metal. The metal constituting the conductive portion is not particularly limited. The conductive metal is not particularly limited. The metal constituting the conductive portion and the conductive metal may be the same metal or different metals. It is preferable that the metal most abundant in the conductive portion and the metal most abundant in the conductive metal are the same.
[0089] Examples of the metal constituting the conductive part and the conductive metal include gold, silver, palladium, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum, and alloys thereof. Examples of the metal constituting the conductive part and the conductive metal include tin-doped indium oxide (ITO) and solder. Only one type of metal constituting the conductive part and the conductive metal may be used, or two or more types may be used in combination.
[0090] From the viewpoint of more effectively lowering the connection resistance between the electrodes, the conductive portion preferably contains nickel, gold, palladium, silver, or copper, and more preferably contains nickel, gold, or palladium.
[0091] The nickel content in 100% by weight of the nickel-containing conductive part is preferably 10% by weight or more, more preferably 50% by weight or more, even more preferably 60% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more. The nickel content in 100% by weight of the nickel-containing conductive part may be 97% by weight or more, 97.5% by weight or more, or 98% by weight or more.
[0092] In addition, hydroxyl groups are often present on the surface of the conductive part due to oxidation. In general, hydroxyl groups are present on the surface of the conductive part formed of nickel due to oxidation. An insulating material can be arranged on the surface of the conductive part (surface of the conductive particle) having such hydroxyl groups via chemical bonding.
[0093] The conductive part may be formed of one layer. The conductive part may be formed of multiple layers. That is, the conductive part may have a laminated structure of two or more layers. When the conductive part is formed of multiple layers, the metal constituting the outermost layer is preferably gold, nickel, palladium, copper, or an alloy containing tin and silver, and more preferably gold. When the metal constituting the outermost layer is one of these preferred metals, the connection resistance between the electrodes is further reduced. In addition, when the metal constituting the outermost layer is gold, the corrosion resistance is further increased.
[0094] The method of forming the conductive portion on the surface of the base particle is not particularly limited. Examples of the method of forming the conductive portion include electroless plating, electroplating, physical collision, mechanochemical reaction, physical vapor deposition or physical adsorption, and a method of coating the surface of the base particle with a metal powder or a paste containing a metal powder and a binder. The method of forming the conductive portion is preferably electroless plating, electroplating, or a physical collision method. Examples of the physical vapor deposition method include vacuum deposition, ion plating, and ion sputtering. Examples of the physical collision method include a sheeter composer (manufactured by Tokuju Kosakusho Co., Ltd.).
[0095] The method of containing the conductive metal inside the base particle is not particularly limited. The method of containing the conductive metal inside the base particle includes a method of electroless plating using the base particle (base particle body) which is a porous particle, and a method of electroplating using the base particle (base particle body) which is a porous particle. Since the base particle (base particle body) which is a porous particle has a relatively large number of voids inside the base particle, when forming a conductive part on the surface of the base particle, the conductive part forming material (plating solution, etc.) can be inserted into the fine voids inside the base particle. By precipitating the conductive metal from the conductive part forming material which has entered the inside of the base particle, the conductive metal can be easily contained inside the base particle. The base particle which is a porous particle includes a base particle which satisfies the preferred range of the BET specific surface area and the porosity.
[0096] The thickness of the conductive part is preferably 0.005 μm or more, more preferably 0.01 μm or more, and preferably 10 μm or less, more preferably 1 μm or less, and even more preferably 0.3 μm or less. The thickness of the conductive part is the thickness of the entire conductive part when the conductive part is multi-layered. When the thickness of the conductive part is equal to or more than the lower limit and equal to or less than the upper limit, sufficient conductivity is obtained, and the conductive particles do not become too hard, and the conductive particles can be sufficiently deformed when connecting between electrodes.
[0097] When the conductive part is formed of a plurality of layers, the thickness of the conductive part of the outermost layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, and preferably 0.5 μm or less, more preferably 0.1 μm or less. When the thickness of the conductive part of the outermost layer is equal to or more than the lower limit and equal to or less than the upper limit, the coating of the conductive part of the outermost layer becomes uniform, the corrosion resistance becomes sufficiently high, and the connection resistance between the electrodes can be sufficiently low. In addition, when the metal constituting the outermost layer is gold, the thinner the thickness of the outermost layer, the lower the cost can be.
[0098] The thickness of the conductive part can be measured by observing the cross section of the conductive particle using, for example, a transmission electron microscope (TEM). The thickness of the conductive part is preferably calculated as the average value of the thicknesses of five arbitrary conductive parts as the thickness of the conductive part of one conductive particle, and more preferably calculated as the average value of the thickness of the entire conductive part as the thickness of the conductive part of one conductive particle. The thickness of the conductive part is preferably determined by calculating the average thickness of the conductive part of each of 10 arbitrary conductive particles.
[0099] In 100% by volume of the conductive particles, the content of the conductive metal is preferably 5% by volume or more, more preferably 10% by volume or more, and preferably 70% by volume or less, more preferably 50% by volume or less. When the content of the conductive metal is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. In addition, when the content of the conductive metal is equal to or more than the lower limit and equal to or less than the upper limit, the insulation reliability between the electrodes can be more effectively improved. In addition, when the content of the conductive metal is equal to or more than the lower limit and equal to or less than the upper limit, the adhesion of the conductive part in the conductive particles can be more effectively increased, and the occurrence of peeling of the conductive part in the conductive particles can be more effectively suppressed. From the viewpoint of further improving the compression characteristics of the conductive particles, the content of the conductive metal in 100% by volume of the conductive particles is preferably 5% by volume or more, more preferably 10% by volume or more, and preferably 50% by volume or less, more preferably 40% by volume or less. From the viewpoint of more effectively lowering the connection resistance between electrodes, the content of the conductive metal in 100% by volume of the conductive particles is preferably 10% by volume or more, more preferably 20% by volume or more, and preferably 50% by volume or less, more preferably 40% by volume or less. In 100% by volume of the conductive particles, the content of the conductive metal is particularly preferably 10% by volume or more and 40% by volume or less. When the content of the conductive metal is within the range of 10% by volume or more and 40% by volume or less, both of improving the compression characteristics of the conductive particles and lowering the connection resistance between the electrodes can be achieved at a higher level. The content of the conductive metal means the total content of the metal constituting the conductive portion and the conductive metal contained in the inside of the base particle. It is preferable to judge whether the conductive metal is contained in the inside of the base particle by the first ratio and the second ratio described later.
[0100] The content of the conductive metal can be calculated as follows.
[0101] Conductive metal content (volume%) = D x M / Dmetal x 100 D: Specific gravity of conductive particles M: Metallization rate of conductive particles Dmetal: Specific gravity of conductive metal
[0102] The metallization rate of the conductive particles can be calculated using ICP emission analysis, and the specific gravity of the conductive particles can be measured using a true specific gravity meter. The specific gravity of the conductive metal can be calculated using a value specific to the metal. The metallization rate of the conductive particles refers to the content (g) of the conductive metal contained in 1 g of the conductive particles expressed as a ratio, that is, the content (g) of the conductive metal contained in 1 g of the conductive particles / 1 g of the conductive particles.
[0103] In the conductive particles (100 vol%), the content of the conductive metal contained in the base particle is preferably 0.1 vol% or more, more preferably 1 vol% or more, and preferably 30 vol% or less, more preferably 20 vol% or less. When the content of the conductive metal is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. In addition, when the content of the conductive metal is equal to or more than the lower limit and equal to or less than the upper limit, the adhesion of the conductive part of the conductive particle can be more effectively increased, and the occurrence of peeling of the conductive part of the conductive particle can be more effectively suppressed.
[0104] From the viewpoint of further improving the compression characteristics of the conductive particles, the content of the conductive metal contained in the conductive part is preferably 0.1 vol% or more, more preferably 1 vol% or more, and preferably 30 vol% or less, more preferably 20 vol% or less, in 100 vol% of the conductive particles. From the viewpoint of further effectively lowering the connection resistance between electrodes, the content of the conductive metal contained in the conductive part is preferably 0.1 vol% or more, more preferably 1 vol% or more, and preferably 30 vol% or less, more preferably 20 vol% or less, in 100 vol% of the conductive particles.
[0105] (core substance) The conductive particles preferably have protrusions on the outer surface of the conductive part. The conductive particles preferably have protrusions on the conductive surface. The protrusions are preferably multiple. An oxide film is often formed on the surface of the electrodes connected by the conductive particles. When conductive particles having protrusions on the surface of the conductive part are used, the oxide film can be effectively removed by the protrusions by arranging the conductive particles between the electrodes and pressing them together. Therefore, the electrodes and the conductive part are in more reliable contact, and the connection resistance between the electrodes is further reduced. Furthermore, when the conductive particles have an insulating material, or when the conductive particles are dispersed in a binder resin and used as a conductive material, the protrusions of the conductive particles can more effectively remove the insulating material or binder resin between the conductive particles and the electrodes. Therefore, the connection resistance between the electrodes can be further reduced.
[0106] When the core material is made of a metal and exists within the conductive portion, the core material is considered to be a part of the conductive portion.
[0107] Examples of the method for forming the protrusions include a method in which a core material is attached to the surface of a base particle, and then a conductive portion is formed by electroless plating, and a method in which a conductive portion is formed on the surface of a base particle by electroless plating, and then a core material is attached, and then a conductive portion is formed by electroless plating, etc. Also, the core material does not have to be used to form the protrusions.
[0108] Other methods for forming the protrusions include a method of adding a core substance during the process of forming a conductive portion on the surface of a base particle, etc. Alternatively, to form the protrusions, a method may be used in which, without using the core substance, a conductive portion is formed on the base particle by electroless plating, a plating is deposited in the form of protrusions on the surface of the conductive portion, and the conductive portion is further formed by electroless plating, etc.
[0109] Examples of the method for attaching the core substance to the surface of the base particle include a method of adding the core substance to a dispersion liquid of the base particle, and accumulating and attaching the core substance to the surface of the base particle by van der Waals force, and a method of adding the core substance to a container containing the base particle, and attaching the core substance to the surface of the base particle by mechanical action such as rotating the container, etc. From the viewpoint of controlling the amount of the core substance to be attached, the method for attaching the core substance to the surface of the base particle is preferably a method of accumulating and attaching the core substance to the surface of the base particle in the dispersion liquid.
[0110] The materials constituting the core material include conductive materials and non-conductive materials. The conductive materials include conductive non-metals such as metals, metal oxides, and graphite, and conductive polymers. The conductive polymers include polyacetylene. The non-conductive materials include silica, alumina, and zirconia. From the viewpoint of more effectively removing the oxide film, it is preferable that the core material is hard. From the viewpoint of more effectively lowering the connection resistance between the electrodes, it is preferable that the core material is a metal.
[0111] The metal is not particularly limited. Examples of the metal include gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium, and cadmium, as well as alloys consisting of two or more metals, such as tin-lead alloy, tin-copper alloy, tin-silver alloy, tin-lead-silver alloy, and tungsten carbide. From the viewpoint of more effectively lowering the connection resistance between the electrodes, the metal is preferably nickel, copper, silver, or gold. The metal may be the same as or different from the metal constituting the conductive portion (conductive layer).
[0112] The shape of the core material is not particularly limited. The core material is preferably in the form of a lump. Examples of the core material include a particulate lump, an aggregate of a plurality of microparticles, and an amorphous lump.
[0113] The particle size of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, and preferably 0.9 μm or less, more preferably 0.2 μm or less. When the particle size of the core material is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced.
[0114] The particle diameter of the core material is preferably an average particle diameter, and more preferably a number average particle diameter. The particle diameter of the core material is determined by observing 50 arbitrary core materials with an electron microscope or optical microscope and calculating the average particle diameter of each core material, or by using a particle size distribution measuring device. In the observation with an electron microscope or optical microscope, the particle diameter of each core material is determined as the particle diameter of a circle equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle diameter of 50 arbitrary core materials with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each core material is determined as the particle diameter of a sphere equivalent diameter. The average particle diameter of the core material is preferably calculated using a particle size distribution measuring device.
[0115] The number of the protrusions per conductive particle is preferably 3 or more, more preferably 5 or more. The upper limit of the number of the protrusions is not particularly limited. The upper limit of the number of the protrusions can be appropriately selected in consideration of the particle diameter of the conductive particles. When the number of the protrusions is equal to or more than the lower limit, the connection resistance between the electrodes can be more effectively reduced.
[0116] The number of protrusions can be calculated by observing any conductive particle with an electron microscope or an optical microscope. The number of protrusions is preferably determined by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average number of protrusions on each conductive particle.
[0117] The height of the protrusions is preferably 0.001 μm or more, more preferably 0.05 μm or more, and is preferably 0.9 μm or less, more preferably 0.2 μm or less. When the height of the protrusions is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be reduced more effectively.
[0118] The height of the protrusions can be calculated by observing the protrusions of any conductive particle with an electron microscope or an optical microscope. The height of the protrusions is preferably calculated by taking the average value of the heights of all the protrusions per conductive particle as the height of the protrusions of one conductive particle. The height of the protrusions is preferably determined by calculating the average value of the heights of the protrusions of 50 arbitrary conductive particles.
[0119] (Insulating material) The conductive particles preferably have an insulating material disposed on the outer surface of the conductive portion. In this case, when the conductive particles are used for connecting electrodes, short-circuiting between adjacent electrodes can be prevented more effectively. Specifically, when a plurality of conductive particles contact each other, an insulating material exists between the plurality of electrodes, so that short-circuiting between adjacent electrodes in the horizontal direction, rather than between upper and lower electrodes, can be prevented. In addition, when connecting electrodes, the insulating material between the conductive portion of the conductive particles and the electrodes can be easily removed by pressing the conductive particles with two electrodes. Furthermore, when the conductive particles have protrusions on the outer surface of the conductive portion, the insulating material between the conductive portion of the conductive particles and the electrodes can be more easily removed.
[0120] The insulating material is preferably insulating particles, since this allows the insulating material to be removed more easily when the electrodes are pressed together.
[0121] Examples of the material of the insulating substance include the above-mentioned organic materials, the above-mentioned inorganic materials, and the above-mentioned inorganic substances as the materials of the base particle, etc. The material of the insulating substance is preferably the above-mentioned organic material.
[0122] Other materials for the insulating material include polyolefin compounds, (meth)acrylate polymers, (meth)acrylate copolymers, block polymers, thermoplastic resins, crosslinked products of thermoplastic resins, thermosetting resins, water-soluble resins, etc. Only one type of the insulating material may be used, or two or more types may be used in combination.
[0123] Examples of the polyolefin compound include polyethylene, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid ester copolymer. Examples of the (meth)acrylate polymer include polymethyl (meth)acrylate, polydodecyl (meth)acrylate, and polystearyl (meth)acrylate. Examples of the block polymer include polystyrene, styrene-acrylic acid ester copolymer, SB type styrene-butadiene block copolymer, SBS type styrene-butadiene block copolymer, and hydrogenated products thereof. Examples of the thermoplastic resin include vinyl polymers and vinyl copolymers. Examples of the thermosetting resin include epoxy resin, phenolic resin, and melamine resin. Examples of the crosslinked thermoplastic resin include the introduction of polyethylene glycol methacrylate, alkoxylated trimethylolpropane methacrylate, and alkoxylated pentaerythritol methacrylate. Examples of the water-soluble resin include polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyvinylpyrrolidone, polyethylene oxide, and methyl cellulose. In addition, a chain transfer agent may be used to adjust the degree of polymerization. Examples of the chain transfer agent include thiol and carbon tetrachloride.
[0124] The method of disposing the insulating material on the surface of the conductive part includes a chemical method, and a physical or mechanical method. The chemical method includes an interfacial polymerization method, a suspension polymerization method in the presence of particles, and an emulsion polymerization method. The physical or mechanical method includes a spray drying method, a hybridization method, an electrostatic adhesion method, a spraying method, a dipping method, and a vacuum deposition method. From the viewpoint of more effectively increasing the insulation reliability and the conduction reliability when the electrodes are electrically connected, the method of disposing the insulating material on the surface of the conductive part is preferably a physical method.
[0125] The outer surface of the conductive part and the outer surface of the insulating material may each be coated with a compound having a reactive functional group. The outer surface of the conductive part and the outer surface of the insulating material may not be directly chemically bonded, and may be indirectly chemically bonded by a compound having a reactive functional group. After a carboxyl group is introduced onto the outer surface of the conductive part, the carboxyl group may be chemically bonded to a functional group on the outer surface of the insulating material via a polymer electrolyte such as polyethyleneimine.
[0126] When the insulating material is an insulating particle, the particle diameter of the insulating particle can be appropriately selected depending on the particle diameter of the conductive particle and the use of the conductive particle. The particle diameter of the insulating particle is preferably 10 nm or more, more preferably 100 nm or more, even more preferably 300 nm or more, particularly preferably 500 nm or more, and preferably 4000 nm or less, more preferably 2000 nm or less, even more preferably 1500 nm or less, particularly preferably 1000 nm or less. If the particle diameter of the insulating particle is the above lower limit or more, when the conductive particle is dispersed in the binder resin, the conductive parts of the multiple conductive particles are less likely to contact each other. If the particle diameter of the insulating particle is the above upper limit or less, it is not necessary to apply too much pressure or heat to a high temperature in order to remove the insulating particles between the electrodes and the conductive particles when connecting the electrodes.
[0127] The particle diameter of the insulating particles is preferably an average particle diameter, and is preferably a number average particle diameter. The particle diameter of the insulating particles is obtained by observing 50 arbitrary insulating particles with an electron microscope or an optical microscope and calculating the average particle diameter of each insulating particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or an optical microscope, the particle diameter of each insulating particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary insulating particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each insulating particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the insulating particles is preferably calculated using a particle size distribution measuring device. When the particle diameter of the insulating particles in the conductive particles is measured, it can be measured, for example, as follows.
[0128] Conductive particles are added to Kulzer's Technovit 4000 so that the content is 30% by weight, and dispersed to prepare a resin for embedding conductive particles for testing. A cross section of the conductive particles is cut out using an ion milling device (Hitachi High-Technologies' IM4000) so as to pass through the center of the dispersed conductive particles in the resin for testing. Then, using a field emission scanning electron microscope (FE-SEM) set to an image magnification of 50,000 times, 50 conductive particles are randomly selected, and the insulating particles of each conductive particle are observed. The particle diameter of the insulating particles in each conductive particle is measured, and the particle diameter of the insulating particles is determined by arithmetic averaging.
[0129] The ratio of the particle size of the conductive particles to the particle size of the insulating particles (particle size of conductive particles / particle size of insulating particles) is preferably at least 4, more preferably at least 8, and is preferably at most 200, more preferably at most 100. When the ratio (particle size of conductive particles / particle size of insulating particles) is at least the lower limit and at most the upper limit, the insulation reliability and conduction reliability can be more effectively improved when electrodes are electrically connected.
[0130] (Conductive materials) The conductive material according to the present invention includes the conductive particles and a binder resin. The conductive particles are preferably dispersed in the binder resin and used, and are preferably dispersed in the binder resin and used as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive material is preferably used for electrical connection between electrodes. The conductive material is preferably a conductive material for circuit connection. Since the conductive material uses the conductive particles described above, the connection resistance between electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. Since the conductive material uses the conductive particles described above, the insulation reliability between the electrodes can be more effectively improved.
[0131] The conductive material preferably contains a plurality of the conductive particles. When a region R1 is a region from the outer surface of the base particle toward the center at a distance of 1 / 2 the particle diameter of the base particle, the ratio of the number of conductive particles in which the conductive metal is present in the region R1 of the base particle to the total number of conductive particles (hereinafter, sometimes referred to as the first ratio) is preferably 50% or more, more preferably 60% or more. The upper limit of the first ratio is not particularly limited. The first ratio may be 100% or less. When the first ratio is equal to or greater than the lower limit, the connection resistance between the electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the first ratio is equal to or greater than the lower limit and equal to or less than the upper limit, the adhesion of the conductive part of the conductive particle can be more effectively increased, and the occurrence of peeling of the conductive part of the conductive particle can be more effectively suppressed. When the first ratio is greater than 0%, it can be determined that the conductive metal is contained inside the base particle. The region R1 is a region outside the dashed line L1 of the base particle 2 in Fig. 4. The region R1 is an outer surface portion of the base particle. The region R1 is a region different from the central portion of the base particle.
[0132] When a region R2 is a region from the center of the base particle toward the outer surface at a distance of 1 / 2 the particle diameter of the base particle, the ratio of the number of conductive particles in which the conductive metal is present in the region R2 of the base particle to the total number of conductive particles (100%) (hereinafter, sometimes referred to as the second ratio) is preferably 5% or more, more preferably 10% or more. The upper limit of the second ratio is not particularly limited. The second ratio may be 100% or less. When the second ratio is equal to or greater than the lower limit, the connection resistance between the electrodes can be more effectively reduced, and the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the second ratio is equal to or greater than the lower limit, the insulation reliability between the electrodes can be more effectively improved. When the second ratio is equal to or greater than the lower limit and equal to or less than the upper limit, the adhesion of the conductive part of the conductive particle can be more effectively increased, and the occurrence of peeling of the conductive part of the conductive particle can be more effectively suppressed. When the second ratio is greater than 0%, it can be determined that the conductive metal is contained inside the base particle. The region R2 is a region inside the broken line L1 of the base particle 2 in Fig. 4. The region R2 is a central portion of the base particle. The region R2 is a region different from the outer surface portion of the base particle.
[0133] The first ratio and the second ratio can be calculated as follows.
[0134] Conductive particles are collected from the conductive material by filtration or the like. The collected conductive particles are added to "Technovit 4000" manufactured by Kulzer so that the content of the conductive particles is 30% by weight, and dispersed to prepare a conductive particle inspection embedding resin. A cross section of one conductive particle is cut out using an ion milling device ("IM4000" manufactured by Hitachi High-Technologies Corporation) so as to pass through the vicinity of the center of the conductive particles dispersed in the embedding resin for inspection. Then, the presence or absence of conductive metal in the cross section of the base particle is measured by an energy dispersive X-ray analyzer (EDS) using a field emission transmission electron microscope ("JEM-2010FEF" manufactured by JEOL Ltd.), thereby obtaining the distribution result of the conductive metal in the particle diameter direction of the base particle. The first ratio and the second ratio can be calculated from the distribution result of the conductive metal in 20 arbitrarily selected conductive particles.
[0135] The binder resin is not particularly limited. A known insulating resin is used as the binder resin. The binder resin preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. Examples of the curable component include a photocurable component and a thermosetting component. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent.
[0136] Examples of the binder resin include vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers, elastomers, etc. The binder resins may be used alone or in combination of two or more.
[0137] Examples of the vinyl resin include vinyl acetate resin, acrylic resin, and styrene resin. Examples of the thermoplastic resin include polyolefin resin, ethylene-vinyl acetate copolymer, and polyamide resin. Examples of the curable resin include epoxy resin, urethane resin, polyimide resin, and unsaturated polyester resin. The curable resin may be a room temperature curable resin, a thermosetting resin, a photocurable resin, or a moisture curable resin. The curable resin may be used in combination with a curing agent. Examples of the thermoplastic block copolymer include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated product of styrene-butadiene-styrene block copolymer, and hydrogenated product of styrene-isoprene-styrene block copolymer. Examples of the elastomer include styrene-butadiene copolymer rubber, and acrylonitrile-styrene block copolymer rubber.
[0138] In addition to the conductive particles and the binder resin, the conductive material may contain various additives such as, for example, a filler, an extender, a softener, a plasticizer, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.
[0139] The method for dispersing the conductive particles in the binder resin can be a conventionally known dispersion method, and is not particularly limited. Examples of the method for dispersing the conductive particles in the binder resin include the following methods. A method in which the conductive particles are added to the binder resin, and then kneaded and dispersed with a planetary mixer or the like. A method in which the conductive particles are uniformly dispersed in water or an organic solvent using a homogenizer or the like, and then added to the binder resin, and then kneaded and dispersed with a planetary mixer or the like. A method in which the binder resin is diluted with water or an organic solvent, and then the conductive particles are added, and then kneaded and dispersed with a planetary mixer or the like.
[0140] The viscosity (η25) of the conductive material at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, and preferably 400 Pa·s or less, more preferably 300 Pa·s or less. When the viscosity of the conductive material at 25°C is equal to or more than the lower limit and equal to or less than the upper limit, the insulation reliability between the electrodes can be more effectively improved, and the conduction reliability between the electrodes can be more effectively improved. The viscosity (η25) can be appropriately adjusted by the types and amounts of the blended components.
[0141] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 5 rpm.
[0142] The conductive material according to the present invention can be used as a conductive paste, a conductive film, or the like. When the conductive material according to the present invention is a conductive film, a film not containing conductive particles may be laminated on a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.
[0143] In 100% by weight of the conductive material, the content of the binder resin is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, particularly preferably 70% by weight or more, and is preferably 99.99% by weight or less, more preferably 99.9% by weight or less. When the content of the binder resin is equal to or more than the lower limit and equal to or less than the upper limit, the conductive particles are efficiently arranged between the electrodes, and the connection reliability of the connection target members connected by the conductive material can be further improved.
[0144] In 100% by weight of the conductive material, the content of the conductive particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and is preferably 80% by weight or less, more preferably 60% by weight or less, even more preferably 40% by weight or less, particularly preferably 20% by weight or less, and most preferably 10% by weight or less. When the content of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced. When the content of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the conduction reliability and insulation reliability between the electrodes can be more effectively improved.
[0145] (Connection structure) The connection structure according to the present invention comprises a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection part connecting the first connection target member and the second connection target member. In the connection structure according to the present invention, the material of the connection part is the conductive particles described above, or a conductive material containing the conductive particles and a binder resin. In the connection structure according to the present invention, the first electrode and the second electrode are electrically connected by the conductive particles.
[0146] The connection structure can be obtained through a step of disposing the conductive particles or the conductive material between the first connection target member and the second connection target member, and a step of conductively connecting the first and second connection target members by thermocompression bonding. When the conductive particles have the insulating material, it is preferable that the insulating material be released from the conductive particles during the thermocompression bonding.
[0147] When the conductive particles are used alone, the connection part itself is a conductive particle. That is, the first connection target member and the second connection target member are connected by the conductive particles. The conductive material used to obtain the connection structure is preferably an anisotropic conductive material.
[0148] FIG. 5 is a schematic front cross-sectional view showing a connection structure using conductive particles according to a first embodiment of the present invention.
[0149] A connection structure 51 shown in Fig. 5 includes a first connection target member 52, a second connection target member 53, and a connection portion 54 connecting the first and second connection target members 52, 53. The connection portion 54 is formed by curing a conductive material containing conductive particles 1. Note that in Fig. 5, the conductive particles 1 are shown in a simplified diagram for convenience of illustration. Instead of the conductive particles 1, other conductive particles such as conductive particles 11, 21, etc. may be used.
[0150] The first connection target member 52 has a plurality of first electrodes 52a on its surface (upper surface). The second connection target member 53 has a plurality of second electrodes 53a on its surface (lower surface). The first electrodes 52a and the second electrodes 53a are electrically connected by one or more conductive particles 1. Therefore, the first and second connection target members 52 and 53 are electrically connected by the conductive particles 1.
[0151] The method for producing the connection structure is not particularly limited. An example of the method for producing the connection structure includes a method in which the conductive material is placed between a first connection target member and a second connection target member, a laminate is obtained, and then the laminate is heated and pressurized. The pressure of the thermocompression bonding is preferably 40 MPa or more, more preferably 60 MPa or more, and preferably 90 MPa or less, more preferably 70 MPa or less. The heating temperature of the thermocompression bonding is preferably 80°C or more, more preferably 100°C or more, and preferably 140°C or less, more preferably 120°C or less. When the pressure and temperature of the thermocompression bonding are equal to or more than the lower limit and equal to or less than the upper limit, the conductive reliability and insulating reliability between the electrodes can be further improved. In addition, when the conductive particles have the insulating particles, the insulating particles can be easily detached from the surface of the conductive particles during conductive connection.
[0152] When the conductive particles have the insulating particles, the insulating particles present between the conductive particles and the first and second electrodes can be eliminated when the laminate is heated and pressed. For example, during the heating and pressing, the insulating particles present between the conductive particles and the first and second electrodes are easily detached from the surface of the conductive particles. During the heating and pressing, some of the insulating particles may be detached from the surface of the conductive particles, causing the surface of the conductive part to be partially exposed. The exposed part of the surface of the conductive part contacts the first electrode and the second electrode, thereby electrically connecting the first electrode and the second electrode through the conductive particles.
[0153] Furthermore, since the connection structure according to the present invention uses the conductive particles described above, when the conductive particles are compressed during the heating and pressurization, not only is a conductive path formed on the surface (conductive portion) of the conductive particles, but the conductive metals inside the conductive particles also come into contact with each other to form a conductive path. As a result, even if the thickness of the conductive portion is relatively thin, the connection resistance between the electrodes in the vertical direction can be sufficiently reduced. In addition, since the thickness of the conductive portion is relatively thin, the occurrence of aggregation of the conductive particles can be suppressed, and the insulation reliability between horizontally adjacent electrodes that should not be connected can be effectively improved.
[0154] The first and second connection target members are not particularly limited. Specific examples of the first and second connection target members include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, as well as electronic components such as resin films, printed circuit boards, flexible printed circuit boards, flexible flat cables, rigid flexible boards, glass epoxy boards, and glass boards. The first and second connection target members are preferably electronic components.
[0155] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, silver electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.
[0156] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0157] Example 1 (1) Preparation of base particles Polystyrene particles with an average particle size of 0.5 μm were prepared as seed particles. 3.9 parts by weight of the polystyrene particles, 500 parts by weight of ion-exchanged water, and 120 parts by weight of a 5% by weight aqueous polyvinyl alcohol solution were mixed to prepare a mixed liquid. The mixed liquid was dispersed by ultrasonic waves, then placed in a separable flask and stirred uniformly.
[0158] Next, 150 parts by weight of divinylbenzene (monomer component), 2 parts by weight of 2,2'-azobis(methyl isobutyrate) ("V-601" manufactured by Wako Pure Chemical Industries, Ltd.), and 2 parts by weight of benzoyl peroxide ("Niper BW" manufactured by NOF Corp.) were mixed. Furthermore, 9 parts by weight of triethanolamine lauryl sulfate, 50 parts by weight of toluene (solvent), and 1100 parts by weight of ion-exchanged water were added to prepare an emulsion.
[0159] The above emulsion was added in several portions to the above mixture in the separable flask, and the mixture was stirred for 12 hours to allow the seed particles to absorb the monomer, thereby obtaining a suspension containing seed particles swollen with the monomer.
[0160] Thereafter, 490 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol was added, and heating was started to carry out a reaction at 85° C. for 9 hours, to obtain base particles having a particle diameter of 2.0 μm.
[0161] (2) Preparation of conductive particles The obtained base particles were washed and dried, and then 10 parts by weight of the base particles were dispersed in 1000 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution using an ultrasonic disperser, and the solution was filtered to extract the base particles. Next, the base particles were added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surface of the base particles. The surface-activated base particles were thoroughly washed with water, and then added to 500 parts by weight of distilled water and dispersed to obtain a dispersion. Next, 1 g of nickel particle slurry (average particle diameter 100 nm) was added to the above dispersion over 3 minutes to obtain a suspension containing base particles to which a core material was attached.
[0162] In addition, a nickel plating solution (pH 8.5) containing 0.35 mol / L of nickel sulfate, 1.38 mol / L of dimethylamine borane, and 0.5 mol / L of sodium citrate was prepared.
[0163] While stirring the obtained suspension at 60° C., 300 parts by weight of the nickel plating solution was gradually dropped into the suspension to perform electroless nickel plating. The suspension was then filtered to extract particles, which were then washed with water and dried to form a nickel-boron conductive layer on the surface of the base particle, thereby obtaining conductive particles having a conductive portion on the surface.
[0164] (3) Preparation of conductive material (anisotropic conductive paste) 7 parts by weight of the obtained conductive particles, 25 parts by weight of bisphenol A type phenoxy resin, 4 parts by weight of fluorene type epoxy resin, 30 parts by weight of phenol novolac type epoxy resin, and SI-60L (manufactured by Sanshin Chemical Industry Co., Ltd.) were mixed together, and the mixture was degassed and stirred for 3 minutes to obtain a conductive material (anisotropic conductive paste).
[0165] (4) Fabrication of connection structure A transparent glass substrate was prepared on which an IZO electrode pattern (first electrode, Vickers hardness of metal on the electrode surface is 100Hv) with L / S of 10μm / 10μm was formed on the upper surface. A semiconductor chip was also prepared on which an Au electrode pattern (second electrode, Vickers hardness of metal on the electrode surface is 50Hv) with L / S of 10μm / 10μm was formed on the lower surface. The obtained anisotropic conductive paste was applied to a thickness of 30μm on the transparent glass substrate to form an anisotropic conductive paste layer. Next, the semiconductor chip was laminated on the anisotropic conductive paste layer so that the electrodes faced each other. Thereafter, a pressurized heating head was placed on the upper surface of the semiconductor chip while adjusting the temperature of the head so that the temperature of the anisotropic conductive paste layer was 100℃, and a pressure of 85MPa was applied to harden the anisotropic conductive paste layer at 100℃ to obtain a connection structure.
[0166] Example 2 Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the blending amount of the solvent was 10 parts by weight when preparing the base particles.
[0167] Example 3 Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the blending amount of the solvent was 70 parts by weight when preparing the base particles.
[0168] Example 4 A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the amount of base particles mixed was 5 parts by weight when the conductive particles were produced.
[0169] Example 5 A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the amount of base particles mixed was 2.5 parts by weight when the conductive particles were prepared.
[0170] Example 6 Conductive particles obtained in Example 1 were prepared. In addition, 5 g of potassium gold cyanide was added to 500 g of a solution containing 10 g / L ethylenediamine tetrasodium acetate and 10 g / L sodium citrate to prepare a gold plating solution. 10 parts by weight of the conductive particles obtained in Example 1 were placed in 500 parts by weight of the gold plating solution and immersed at 70°C for 30 minutes to perform electroless gold plating. Thereafter, the suspension was filtered to remove the particles, which were washed with water and dried to form a nickel-boron-gold conductive layer on the surface of the base particle, thereby obtaining conductive particles having a conductive portion on the surface. A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the obtained conductive particles were used.
[0171] Example 7 A suspension was obtained by adding 10 parts by weight of the conductive particles obtained in Example 1 to 200 parts by weight of distilled water and dispersing them. A palladium plating solution containing 10 g / L ethylenediamine, 3.0 g / L palladium sulfate, and 5.0 g / L sodium formate was also prepared. The suspension was heated to 70°C, and then 700 parts by weight of the palladium plating solution was dropped over 10 minutes to perform electroless palladium plating. The suspension was then filtered to remove the particles, which were then washed with water and dried to form a nickel-boron-palladium conductive layer on the surface of the base particle, thereby obtaining conductive particles having a conductive portion on the surface. A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the obtained conductive particles were used.
[0172] Example 8 A suspension was obtained by adding 10 parts by weight of the conductive particles obtained in Example 1 to 200 parts by weight of distilled water and dispersing them. A silver plating solution was prepared by adjusting a mixed solution containing 10 g / L potassium silver cyanide, 80 g / L potassium cyanide, 5 g / L ethylenediaminetetraacetic acid, and 20 g / L sodium hydroxide to pH 6 with sodium hydroxide. The suspension was heated to 50°C, and then 700 parts by weight of the silver plating solution was dropped over 30 minutes to perform electroless silver plating. The suspension was then filtered to remove the particles, which were then washed with water and dried to form a nickel-boron-silver conductive layer on the surface of the base particle, thereby obtaining conductive particles having a conductive portion on the surface. A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the obtained conductive particles were used.
[0173] Example 9 In the preparation of the base particles, the seed particle diameter was changed to obtain base particles having a particle diameter of 1.0 μm. Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the obtained base particles were used and the amount of the obtained base particles was changed to 5 parts by weight.
[0174] Example 10 In the preparation of the base particles, the seed particle diameter was changed to obtain base particles having a particle diameter of 2.5 μm. Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the obtained base particles were used and the amount of the obtained base particles was changed to 12.5 parts by weight.
[0175] Example 11 In the preparation of the base particles, the seed particle diameter was changed to obtain base particles having a particle diameter of 3.0 μm. Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the obtained base particles were used and the amount of the obtained base particles was changed to 15 parts by weight.
[0176] Example 12 In the preparation of the base particles, the seed particle diameter was changed to obtain base particles having a particle diameter of 5.0 μm. Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the obtained base particles were used and the amount of the obtained base particles was changed to 25 parts by weight.
[0177] Example 13 In the preparation of the base particles, the seed particle diameter was changed to obtain base particles having a particle diameter of 10.0 μm. Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the obtained base particles were used and the amount of the obtained base particles was changed to 50 parts by weight.
[0178] Example 14 (1) Preparation of insulating particles The following monomer composition was placed in a 1000 mL separable flask equipped with a four-neck separable cover, stirring blade, three-way cock, cooling tube and temperature probe, and then distilled water was added so that the solid content of the following monomer composition was 10% by weight, and the mixture was stirred at 200 rpm and polymerized at 60°C for 24 hours under a nitrogen atmosphere. The monomer composition contains 360 mmol of methyl methacrylate, 45 mmol of glycidyl methacrylate, 20 mmol of parastyryldiethylphosphine, 13 mmol of ethylene glycol dimethacrylate, 0.5 mmol of polyvinylpyrrolidone, and 1 mmol of 2,2'-azobis{2-[N-(2-carboxyethyl)amidino]propane}. After the reaction was completed, the mixture was freeze-dried to obtain insulating particles (particle diameter 360 nm) having phosphorus atoms derived from parastyryldiethylphosphine on the surface.
[0179] (2) Preparation of conductive particles with insulating particles The insulating particles obtained in (1) above were dispersed in distilled water under ultrasonic irradiation to obtain a 10 wt% aqueous dispersion of insulating particles. 10 g of the conductive particles obtained in Example 1 were dispersed in 500 mL of distilled water, and 1 g of the 10 wt% aqueous dispersion of insulating particles was added and stirred at room temperature for 8 hours. After filtering with a 3 μm mesh filter, the mixture was further washed with methanol and dried to obtain conductive particles with insulating particles. A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the obtained conductive particles with insulating particles were used.
[0180] Example 15 Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the nickel particle slurry (average particle diameter 100 nm) was not used when producing the conductive particles.
[0181] (Example 16) Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the amount of catalyst liquid was changed to 200 parts by weight when producing the conductive particles.
[0182] (Example 17) Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the amount of catalyst liquid was changed to 500 parts by weight when producing the conductive particles.
[0183] (Example 18) The conductive particles obtained in Example 15 were prepared. Using the conductive particles obtained in Example 15, conductive particles with insulating particles were obtained in the same manner as in Example 14. A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the obtained conductive particles with insulating particles were used.
[0184] Comparative Example 1 Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the solvent was changed from toluene to ethanol when preparing the base particles.
[0185] Comparative Example 2 Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Comparative Example 1, except that the amount of base particles mixed was 5 parts by weight when the conductive particles were produced.
[0186] Comparative Example 3 The conductive particles obtained in Comparative Example 2 were prepared. Using the conductive particles obtained in Comparative Example 2, conductive particles with insulating particles were obtained in the same manner as in Example 14. A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the obtained conductive particles with insulating particles were used.
[0187] Comparative Example 4 Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Comparative Example 1, except that the amount of base particles mixed was 20 parts by weight when the conductive particles were produced.
[0188] (evaluation) (1) Particle size of base particles and conductive particles The particle diameters of the obtained base particles and conductive particles were calculated using a particle size distribution measuring device (Multisizer 4 manufactured by Beckman Coulter, Inc.) Specifically, the particle diameters of about 100,000 base particles or conductive particles were measured and the average value was calculated.
[0189] (2) BET specific surface area of base material particles The nitrogen adsorption isotherm of the obtained base particles was measured using a "NOVA4200e" manufactured by Quantachrome Instruments Co., Ltd. From the measurement results, the specific surface area of the base particles was calculated according to the BET method.
[0190] (3) Total pore volume of the substrate particle The nitrogen adsorption isotherm of the obtained base particles was measured using a Quantachrome Instruments "NOVA4200e." From the measurement results, the total pore volume of the base particles was calculated according to the BJH method.
[0191] (4) Average pore size of the substrate particles The nitrogen adsorption isotherm of the obtained base particles was measured using a Quantachrome Instruments "NOVA4200e." From the measurement results, the total pore volume of the base particles was calculated according to the BJH method.
[0192] (5) Porosity of the substrate particles The cumulative amount of mercury intrusion into the obtained base particles was measured against the applied pressure by mercury intrusion porosimetry using a mercury porosimeter "Poremaster 60" manufactured by Quantachrome Instruments Co., Ltd. The porosity of the base particles was calculated from the measurement results.
[0193] (6) Content of conductive metal in 100% by volume of conductive particles For the obtained conductive particles, the content of the conductive metal in 100% by volume of the conductive particles was calculated as follows.
[0194] Conductive metal content (volume%) in 100% conductive particles by volume = D x M / Dmetal x 100 D: Specific gravity of conductive particles M: Metallization rate of conductive particles Dmetal: Specific gravity of conductive metal
[0195] The metallization rate of the conductive particles was calculated using an ICP emission spectrometer ("ICP-AES" manufactured by Horiba, Ltd.). The specific gravity of the conductive particles was measured using a true specific gravity meter ("AccuPic" manufactured by Shimadzu Corporation). The specific gravity of the conductive metal was calculated using a value specific to the metal.
[0196] (7) The content of the conductive metal contained in the base particle in 100% by volume of the conductive particle, and the content of the conductive metal contained in the conductive portion in 100% by volume of the conductive particle For the obtained conductive particles, the content of the conductive metal contained in the conductive portion in 100% by volume of the conductive particles was calculated as follows.
[0197] Conductive metal content (volume %) in the conductive part of 100% conductive particles = D x M1 / Dmetal x 100 M1: Metallization rate of conductive part Dmetal: Specific gravity of conductive metal
[0198] The metallization rate M1 of the conductive part is the ratio of the conductive metal content (g) in the conductive part contained in 1 g of conductive particle, i.e., the conductive metal content (g) in the conductive part contained in 1 g of conductive particle / 1 g of conductive particle.
[0199] The metallization rate M1 of the conductive portion was calculated using the following two relational expressions. A = [(r + t) 3 -r 3 ]d1 / r 3 d2(1) A = M1 / (1-M1) (2) r: radius of substrate particle t: Thickness of the conductive part d1: Specific gravity of conductive metal d2: specific gravity of base material particles M1: Metallization rate of conductive part
[0200] Next, for the obtained conductive particles, the content of the conductive metal contained in the base particle in 100% by volume of the conductive particles was calculated as follows.
[0201] Conductive metal content (volume %) contained in base particles in 100 volume% conductive particles = Conductive metal content (volume %) in 100 volume% conductive particles - Conductive metal content (volume %) contained in conductive part in 100 volume% conductive particles = D x M / Dmetal x 100 - D x M1 / Dmetal x 100 = D x (M-M1) / Dmetal x 100 D: Specific gravity of conductive particles M: Metallization rate of conductive particles M1: Metallization rate of conductive part Dmetal: Specific gravity of conductive metal
[0202] (8) The ratio of the number of conductive particles containing a conductive metal (the first ratio and the second ratio) Using the obtained conductive material, when a region from the outer surface of the base particle toward the center is a region at a distance of 1 / 2 the particle diameter of the base particle, the ratio of the number of conductive particles in which the conductive metal is present in the region R1 of the base particle (first ratio) out of 100% of the total number of conductive particles was calculated as follows: Also, using the obtained conductive material, when a region from the center of the base particle toward the outer surface is a region at a distance of 1 / 2 the particle diameter of the base particle, the ratio of the number of conductive particles in which the conductive metal is present in the region R2 of the base particle out of 100% of the total number of conductive particles (second ratio) was calculated as follows:
[0203] The conductive material obtained was filtered to recover the conductive particles. The recovered conductive particles were added to Kulzer's Technovit 4000 so that the content of the conductive particles was 30% by weight, and dispersed to prepare a conductive particle inspection embedding resin. A cross section of one conductive particle was cut out using an ion milling device (Hitachi High-Technologies Corporation's IM4000) so as to pass through the center of the conductive particles dispersed in the embedding resin for inspection. Then, a field emission transmission electron microscope (JEOL Ltd.'s JEM-2010FEF) was used to measure the presence or absence of conductive metal in the cross section of the base particle with an energy dispersive X-ray analyzer (EDS), thereby obtaining the distribution result of the conductive metal in the particle diameter direction of the base particle. The first ratio and the second ratio were calculated from the distribution result of the conductive metal in 20 arbitrarily selected conductive particles.
[0204] (9) Compressive elastic modulus of conductive particles The compressive elastic modulus (10% K value and 30% K value) of the obtained conductive particles was measured by the above-mentioned method using a microcompression tester (Fisherscope H-100 manufactured by Fischer). The 10% K value and 30% K value were calculated from the measurement results.
[0205] (10) Aggregation of conductive particles The obtained conductive material was observed to check whether or not the conductive particles had agglomerated. The agglomeration of the conductive particles was judged under the following conditions.
[0206] [Criteria for determining agglomeration of conductive particles] ○: No aggregation of conductive particles occurs △: A small amount of conductive particle aggregation occurred. ×: Aggregation of conductive particles occurs
[0207] (11) Adhesion of the conductive part of conductive particles 1.0 g of the obtained conductive particles and 50 g of zirconia beads with a diameter of 1 mm were placed in a 100 mL mayonnaise bottle. Furthermore, 10 mL of toluene was added to the mayonnaise bottle. The contents of the mayonnaise bottle were stirred at 300 rpm for 10 minutes using a stirrer (Three-One Motor). After stirring, the conductive particles and the zirconia beads were separated, and the conductive particles were observed using a scanning electron microscope (SEM) to confirm whether peeling had occurred in the conductive parts of the conductive particles. The adhesion of the conductive parts of the conductive particles was evaluated under the following conditions.
[0208] [Criteria for determining adhesion of conductive parts in conductive particles] ○: No peeling occurred in the conductive part of the conductive particles ×: Peeling occurred in the conductive part of the conductive particle.
[0209] (12) Connection resistance (between upper and lower electrodes) The connection resistance between the upper and lower electrodes of the 20 connection structures obtained was measured by the four-terminal method. The average value of the connection resistance was calculated. Note that, based on the relationship of voltage = current x resistance, the connection resistance can be calculated by measuring the voltage when a constant current is applied. The connection resistance was evaluated according to the following criteria.
[0210] [Connection resistance criteria] ○○○: The average connection resistance is 1.5Ω or less ○○: The average connection resistance is over 1.5Ω and 2.0Ω or less ○: The average connection resistance is greater than 2.0Ω and less than 5.0Ω △: The average connection resistance is over 5.0Ω and 10Ω or less ×: The average connection resistance exceeds 10 Ω
[0211] (13) Insulation reliability (between laterally adjacent electrodes) The 20 connection structures obtained in the above (12) connection reliability evaluation were evaluated for the presence or absence of leakage between adjacent electrodes by measuring the resistance value with a tester. The insulation reliability was evaluated according to the following criteria.
[0212] [Insulation reliability criteria] ○○○: Resistance value is 10 8 Number of connection structures with Ω or more is 20 ○○: Resistance value is 10 8 The number of connection structures with Ω or more is 18 or more and less than 20 ○: Resistance value is 10 8 The number of connection structures of Ω or more is 15 or more but less than 18 △: Resistance value is 10 8 The number of connection structures with Ω or more is 10 or more but less than 15 ×: Resistance value is 10 8 The number of connection structures of Ω or more is less than 10
[0213] The results are shown in Tables 1 to 4 below.
[0214] [Table 1]
[0215] [Table 2]
[0216] [Table 3]
[0217] [Table 4] [Explanation of symbols]
[0218] 1...Conductive particles 2...Base material particles 3...Conductive part 11...Conductive particles 11a...Protrusion 12...Conductive part 12a...Protrusion 13…core substance 14...Insulating materials 21...Conductive particles 21a...Protrusion 22...Conductive part 22a...protrusion 22A…First conductive part 22Aa…Protrusion 22B...Second conductive part 22Ba...Protrusion 51...Connection structure 52...First connection target member 52a...first electrode 53...Second connecting member 53a...second electrode 54…Connection
Claims
1. A conductive portion is provided on a surface of a base particle, The substrate particle contains a conductive metal therein, The conductive particles, wherein the porosity of the base particle is 10% or more and 90% or less.
2. A conductive portion is provided on a surface of a base particle, the base particle is a resin particle, an inorganic particle other than a metal particle, or an organic-inorganic hybrid particle; The substrate particle contains a conductive metal therein, The 30% K value of the conductive particles is 100 N / mm 2 More than 15000N / mm 2 The conductive particles are as follows:
3. A conductive portion is provided on a surface of a base particle, the base particle is a resin particle, an inorganic particle other than a metal particle, or an organic-inorganic hybrid particle; The substrate particle contains a conductive metal therein, A conductive particle, the ratio of a 10% K value of the conductive particle to a 30% K value of the conductive particle being 1.5 or more and 5 or less.
4. A conductive portion is provided on a surface of a base particle, The substrate particle contains a conductive metal therein, Conductive particles, wherein the content of the conductive metal contained in the base particle is 0.1 vol % or more and 30 vol % or less, based on 100 vol % of the conductive particles.
5. The conductive particle according to any one of claims 1 to 4, wherein the conductive metal comprises nickel, gold, palladium, silver, or copper.
6. The conductive particle according to any one of claims 1 to 5, wherein the conductive portion comprises nickel, gold, palladium, silver, or copper.
7. The 10% K value of the conductive particles is 100 N / mm 2 More than 25000N / mm 2 The conductive particle according to any one of claims 1 to 6, wherein:
8. The conductive particles according to any one of claims 1 to 7, wherein the conductive particles have a particle diameter of 0.1 µm or more and 1000 µm or less.
9. The conductive particle according to any one of claims 1 to 8, having protrusions on the outer surface of the conductive portion.
10. The conductive particle according to any one of claims 1 to 9, comprising an insulating material disposed on an outer surface of the conductive portion.
11. A conductive material comprising the conductive particles according to any one of claims 1 to 10 and a binder resin.
12. A plurality of the conductive particles are included, 12. The conductive material according to claim 11, wherein when a region R1 is defined as a region having a distance of 1 / 2 the particle diameter of the base particle from the outer surface toward the center of the base particle, the proportion of the number of conductive particles in which the conductive metal is present in the region R1 of the base particle out of the total number of conductive particles (100%) is 50% or more.
13. A plurality of the conductive particles are included, 13. The conductive material according to claim 11 or 12, wherein when a region R2 is defined as a region having a distance of 1 / 2 the particle diameter of the base particle from the center of the base particle toward the outer surface, the proportion of the number of conductive particles in which the conductive metal is present in the region R2 of the base particle out of the total number of conductive particles (100%) is 5% or more.
14. a first connection target member having a first electrode on a surface thereof; a second connection target member having a second electrode on a surface thereof; a connection portion connecting the first connection target member and the second connection target member, a material for the connection portion is the conductive particle according to any one of claims 1 to 10, or is a conductive material containing the conductive particle and a binder resin; A connection structure, wherein the first electrode and the second electrode are electrically connected by the conductive particles.
Citation Information
Patent Citations
Coated conductive particle, anisotropic conductive material, and conductive connection structure
JP2005203319A
Conductive particle, method for producing the same, method for producing insulated conductive particle, and anisotropic conductive adhesive film
JP2009102731A
Conductive particle
JP2013020721A
Base particle, conductive particle, conductive material, and connection structure
JP2015044987A
Conductive particle, conductive material and connection structure
JP2015057757A